A retrospective cohort study on optimal serum progesterone levels before FET cycles using vaginal and parenteral progesterone supplementation and its pregnancy outcomes - Panneerselvam, Prasanna; K., Yuvashree; Prakash, Swetha; Sritharan, M.; Elanchezhian, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Hormone replacement therapy (HRT) allows the day of embryo transfer to be scheduled and reduces the need for monitoring. We want to evaluate the relationship between serum progesterone (P) levels on the day of embryo transfer and pregnancy outcomes determining an ideal level could enable frozen-thawed embryo transfer (FET) personalization. Methods: This study included 212 women who underwent FET-ICSI cycles. Women were grouped into two groups of administration (vaginal and parenteral) based on the route of progesterone administration. We investigated the correlations between route of progesterone administration and pregnancy outcomes, route of progesterone administration and serum P4 levels and route of progesterone administration and endometrial thickness. Results: Pregnancy outcome in vaginal group was 67.65% and parenteral group was 60.53%. p value was 0.2969, which is statistically insignificant. Median value for vaginal group was 11.60 and for parenteral group, it was 32.90. p value was <0.001, which is statistically significant of serum progesterone. Median value for vaginal group was 8.550 and for parenteral group, it was 8.660, p value was <0.001, which is statistically significant of endometrial thickness. Conclusions: Higher clinical pregnancies are obtained from vaginal group when compared to parenteral group. There was a statistically significant difference while correlating serum P4 value with route of progesterone and there was no statistical difference in the endometrial thickness between the vaginal and parenteral groups.